2007
DOI: 10.1029/2006jd007322
|View full text |Cite
|
Sign up to set email alerts
|

Spectral properties of mesospheric ice clouds: Evidence for nonspherical particles

Abstract: [1] We discuss spectrally resolved measurements of the light scattering by mesospheric ice particles from lidars and satellite-borne instruments in order to test whether Gaussian particle size distributions predicted by microphysical models are consistent with these observations. This study shows that none of the considered data sets is consistent with this assumption as long as spherical particles are assumed whose scattering properties may be described by Mie scattering theory. In addition, lognormal size di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 35 publications
(87 reference statements)
5
43
0
Order By: Relevance
“…Eremenko et al (2005) indicate needle-or plate-like particles with ε ≈ 0.5 or ε ≈ 2. Rapp et al (2007) estimated ε ≈ 0.2 or ε ≈ 7. The most extensive data set is from the SOFIE (Solar Occultation For Ice Experiment) instrument, with mean ε ≈ 0.5 or ε ≈ 2 (Hervig et al, 2009a;Hervig and Gordley, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Eremenko et al (2005) indicate needle-or plate-like particles with ε ≈ 0.5 or ε ≈ 2. Rapp et al (2007) estimated ε ≈ 0.2 or ε ≈ 7. The most extensive data set is from the SOFIE (Solar Occultation For Ice Experiment) instrument, with mean ε ≈ 0.5 or ε ≈ 2 (Hervig et al, 2009a;Hervig and Gordley, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These are the same model runs as previously described and discussed by Rapp et al (2007) in the context of modeling color ratios observed by lidar. The key questions to be addressed with the help of these model runs were: (1) What is the cause for the increase of distribution width with increasing particle size?…”
Section: Model Results and Discussionmentioning
confidence: 99%
“…Jensen and Thomas, 1994;Rapp et al, 2002). For the current study, we use results from a large number of simulations using a one-dimensional version of CARMA which have been described in detail in Rapp and Thomas (2006); Rapp et al (2007).…”
Section: Carmamentioning
confidence: 99%
“…While these two simplifying assumptions have been most commonly used in model simulations, recent model work and comparisons with experimental data (e.g. Baumgarten et al, 2002;Eremenko et al, 2005;Hervig, 2006;Rapp et al, 2007) have shown that a Gaussian size distribution and non-spherical iced particles are more consistent with the observations, and should be considered in the modelling of the PMCs. Rapp et al (2007) have shown that the assumption of spherical particle distribution does not allow a consistent interpretation of available satellite and ground-based observations of PMCs.…”
Section: Model Errorsmentioning
confidence: 99%
“…It has been widely used in the study of the microphysical and physical properties of PMC (e.g. Turco et al, 1982;Jensen and Thomas, 1988;Jensen et al, 1989;Rapp et al, 2002Rapp et al, , 2007Rapp and Thomas, 2006). In the scope of the present study, dust and ice particles are modelled at a latitude of ∼69 • N for the altitude range from 75 to 90 km.…”
Section: The 1-d Carma Modelmentioning
confidence: 99%